Technological solutions for long-term storage of partially used nuclear waste: A critical review - Kurniawan, Tonni Agustiono; Othman, Mohd Hafiz Dzarfan; Singh, Deepak; Avtar, Ram; Hwang, Goh Hui; Setiadi, Tjandra; Lo, Wai-hung (Annals of nuclear energy, 2022)
[Display omitted] •Nuclear power is an ideal option for sustainable energy sources from U-235 fission.•A 1,000 MWe reactor generates about 25–30 m3 of PUNF annually.•Deep geological repository is the most ideal disposal technology for PUNF waste.•Th-232 is an ideal option to replace U-238 as a nuclear fuel.•Vitrification is prone to the risk of nuclear proliferation. Nuclear power is an ideal option for sustainable energy sources from U-235 fission. However, this energy generates long-term radioactive waste such as partially used nuclear fuel (PUNF) during electricity production. This work reviews various technologies to provide viable, sustainable, and long-term solutions for the PUNF storage. They include vitrification, partitioning and transmutation (P&T), pyro-processing, and deep geological repository (DGR). Their benefits and drawbacks are evaluated and compared based on previous studies. How to deal with the public perception of DGR and its impacts on the future of nuclear energy and the business opportunities of nuclear storage technology in the global market are discussed. A perspective of recycling nuclear waste into usable fuel is also elaborated. Our literature survey of 160 published articles (1981–2021) showed that DGR is the most ideal solution for long-term storage of the PUNF, as it provides an ultimate destination in a deep underground that permanently isolates the waste from inhabitants and the environment. Although storing PUNF in a DGR maybe convenient and economical in the short-term, the waste must be stored in a retrievable form so that it can be recycled as a fuel.In the long-term, a complete recycling of used nuclear fuel is the best option. As technological solutions and sound radioactive waste management policy are important for the safe storage of PUNF, stakeholders in the nuclear industry should portray long-term radioactive waste management through viable, feasible, and permanent solutions to waste storage for the sake of public safety and the environment.